2021
DOI: 10.1007/s00068-021-01754-5
|View full text |Cite
|
Sign up to set email alerts
|

Delayed diagnosed trauma in severely injured patients despite guidelines-oriented emergency room treatment: there is still a risk

Abstract: Purpose Emergency trauma room treatment follows established algorithms such as ATLS®. Nevertheless, there are injuries that are not immediately recognized here. The aim of this study was to evaluate the residual risk for manifesting life-threatening injuries despite strict adherence to trauma room guidelines, which is different to missed injuries that describe recognizable injuries. Methods In a retrospective study, we included 2694 consecutive patients ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…In a retrospective study between 2016 and 2019, 2694 consecutive patients were admitted to a level I trauma centre and a strict emergency room algorithm followed. Injuries were missed in seven patients (0.26%; one epidural bleeding and six abdominal hollow organ injuries; two died), which highlights the need for continuous clinical and instrument-based examinations after completion of the tertiary survey [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a retrospective study between 2016 and 2019, 2694 consecutive patients were admitted to a level I trauma centre and a strict emergency room algorithm followed. Injuries were missed in seven patients (0.26%; one epidural bleeding and six abdominal hollow organ injuries; two died), which highlights the need for continuous clinical and instrument-based examinations after completion of the tertiary survey [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies were conducted on ICU patients or those patients with significant and life-threatening injuries. Due to the severity of initial injuries, prioritization of management, and distraction, the number of missed injuries detected at TS in these patients is much higher [ 10 , 12 , 15 , 22 , 24 , 27 ]. Although this result is not relevant to the EDOU cohort, it emphasizes the importance of TTS in all polytrauma patients.…”
Section: Reviewmentioning
confidence: 99%
“…Most studies also concluded satisfactorily that standardized TTS at 24 hours gives better outcomes and is a cost-effective, easy, and efficient tool [ 10 - 12 , 22 - 24 , 27 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation